Changes in species composition, herbaceous biomass yield, soil seedbank and soil properties of semi-arid grassland subjected to different levels of rainfall interception and resting period - Hassen, Abubeker (University of Pretoria, 2023)
Thesis (PhD (Animal Production Management))--University of Pretoria, 2022.